Altered expression of Presenilin2 impacts endolysosomal homeostasis and synapse function in Alzheimer’s disease-relevant brain circuits - Anika Perdok; Zoë P. Van Acker; Céline Vrancx; Ragna Sannerud; Inge Vorsters; Assunta Verrengia; Zsuzsanna Callaerts-Végh; Eline Creemers; Sara Gutiérrez Fernández; Britt D’hauw; Lutgarde Serneels; Keimpe Wierda; et al. (Nature Communications, 2024)
Abstract Rare mutations in the gene encoding presenilin2 (PSEN2) are known to cause familial Alzheimer’s disease (FAD). Here, we explored how altered PSEN2 expression impacts on the amyloidosis, endolysosomal abnormalities, and synaptic dysfunction observed in female APP knock-in mice. We demonstrate that PSEN2 knockout (KO) as well as the FAD-associated N141IKI mutant accelerate AD-related pathologies in female mice. Both models showed significant deficits in working memory that linked to elevated PSEN2 expression in the hippocampal CA3 region. The mossy fiber circuit of APPxPSEN2KO and APPxFADPSEN2 mice had smaller pre-synaptic compartments, distinct changes in synaptic vesicle populations and significantly impaired long term potentiation compared to APPKI mice. At the cellular level, altered PSEN2 expression resulted in endolysosomal defects and lowered surface expression of synaptic proteins. As PSEN2/γ-secretase is restricted to late endosomes/lysosomes, we propose PSEN2 impacts endolysosomal homeostasis, affecting synaptic signaling in AD-relevant vulnerable brain circuits; which could explain how mutant PSEN2 accelerates AD pathogenesis.